Biomass Production of Single Species Cover Crop - G. F. Sassenrath; J. K. Farney (Kansas Agricultural Experiment Station Research Reports, 2019)
Cover crops can benefit agricultural production by improving soil health and productivity, reducing weeds, and providing biomass for grazing. In this one-year study, biomass production was measured in 17 different single species summer cover crops and a fallow control. Overall, grass species produced more biomass than brassicas, with legumes, broadleaves, and fallow yielding intermediate amounts of biomass. Within the grass species, pearl millet, brown midrib (BMR) sorghum, and sorghum sudan produced more biomass than proso millet; German millet and browntop millet had intermediate biomass production. Within the brassicas, both brown and yellow mustards produced more biomass than collards. There was no difference in biomass production within the broadleaf species or the legume species tested. Plots that produced higher amounts of biomass also had fewer weeds, indicating the potential for cover crops to reduce weed growth and establishment. The cost of biomass production varied widely between the cover crops, with the broadleaf and grass species being the least expensive. Choice of a cover crop depends on the goals. Based on cost, weed suppression, and grazing potential, the most suitable cover crops identified in this study were pearl millet, BMR sorghum, sorghum sudan, German millet, okra, and cowpea.
Keywords: cover crop; summer annual; weeds; biomass production